(untitled) - Ngô, Minh Châu (Can Tho, 2009)
The study reported in this thesis aims at testing the effects of the implementation of the process approach to writing instruction on learners' quality of EFL writing and investigating learners' perceptions towards the use of the process-based writing activities in the context of the vietnamese upper-secondary writing classroom.
Keywords: English language,Tiếng Anh,English language,Tiếng Anh; Study and teaching,Dạy và học,Research,Nghiên cứu